2022
DOI: 10.1007/s10924-022-02553-8
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Polyvinyl Alcohol-Piperazine Cross-Linked Polymer for Antibacterial Applications

Abstract: The spread of microbes which cause infectious diseases are of great concern on human health. Therefore, a water-soluble cross-linked polymer based on polyvinyl alcohol was synthesized via an economical, facile, and aqueous-based approach. The resultant cross-linked polymer was characterized by different techniques such as FTIR, 1H NMR, 13C NMR, TGA, and DSC. The IR spectrum has been recorded in the range 400–4000 cm−1. From thermal studies, i.e. TGA, cross-linking polymer PVA-E-Pz showed two step degradation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The enhanced antimicrobial efficacy of the synthesized polymer can be attributed to the presence of the piperazine moiety in its molecular structure, as well as the hydroxyl group of the bifunctional coupler, both of which contribute to its activity against pathogenic microbes, leading to cell lysis. 65…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced antimicrobial efficacy of the synthesized polymer can be attributed to the presence of the piperazine moiety in its molecular structure, as well as the hydroxyl group of the bifunctional coupler, both of which contribute to its activity against pathogenic microbes, leading to cell lysis. 65…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the compelling inhibitory effects against both S. aureus and E. coli indicate the potential of the BPJ polymer as a promising candidate for developing novel antibacterial agents. The comparative study 16,[65][66][67][68][69][70][71] was conducted from previously reported literature and the graph was plotted as shown in Fig. 8.…”
Section: Microbial Colony Count Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of PVA electrolytes was initiated by dissolving 1 g of PVA in 10 mL deionized water and stirring continuously at 60 C for 4 h. The obtained PVA solution was cross-linked by adding 250 μL of Glutaraldehyde, then stirred continuously at 30 C for 1 h. Then stirred again by using 250 μL of HCl as an initiator for a while. [36][37][38] After adding HCl, the pre-gel solution was divided into four different Petri dishes and waited for 2 days to obtain cross-linked PVA solutions. The electrolytes divided into four groups were waited in aqueous solutions of KOH at different concentrations (0.5, 1, 1.5, and 2 M) for 2 days to obtain saturated electrolytes.…”
Section: Methodsmentioning
confidence: 99%